PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN LEVERAGE TERHADAP EARNING RESPONSE COEFFICIENT DENGAN GOOD CORPORATE GOVERNANNCE SEBAGAI VARIABEL MEDIASI - Arini Prihatiningrum; Sri Ayem (Universitas Pembangunan Nasional Veteran Yogyakarta, 2020)
This study aims to analyze the disclosure of Corporate Social Responsibility (CSR) and Leverage on the Earnings Response Coefficient (ERC) by considering Good Corporate Governance as a mediating or intervening variable. The data used in this study are secondary data obtained from several sources. The subjects of this research are state-owned companies listed on the Indonesia Stock Exchange in 2016-2019. The sample of this study were 12 companies with a total of 48 data for 4 years from 2016 to 2019 which were selected by purposive sampling method. The analysis tool is the Classical Assumption Test and Path Analysis. This study found only four hypotheses were accepted, the other hypotheses were rejected. This study concludes that disclosure of Corporate Social Responsibility (CSR) has a positive effect on Good Corporate Governance (GCG), Leverage has a positive effect on Good Corporate Governance (GCG), Disclosure of Corporate Social Responsibility (CSR) has a positive effect on Earning Response Coefficient (ERC), Leverage. It has a positive effect on the Earning Response Coefficient (ERC), and Good Corporate Governance (GCG) is accepted to be added to the model as a mediating or intervening variable. Penelitian ini bertujuan untuk menganalisis pengungkapan Corporate Social Responsibility (CSR) dan Leverage terhadap Earnings Response Coefficient (ERC) dengan mempertimbangkan Good Corporate Governance sebagai variabel mediasi atau intervening. Data yang digunakan dalam penelitian ini adalah data sekunder yang diperoleh dari beberapa sumber. Subjek penelitian ini adalah perusahaan BUMN yang terdaftar di Bursa Efek Indonesia tahun 2016-2019. Sampel penelitian ini adalah 12 perusahaan dengan total 48 data selama 4 tahun dari tahun 2016 hingga 2019 yang dipilih dengan purposive sampling method. Alat analisis adalah Uji Asumsi Klasik dan Path Analysis. Penelitian ini menemukan hanya empat hipotesis yang diterima, hipotesis lainnya ditolak. Penelitian ini menyimpulkan bahwa Pengungkapan Corporate Social Responsibility (CSR) berpengaruh positif terhadap Good Corporate Governance (GCG), Leverage berpengaruh positif terhadap Good Corporate Governance (GCG), Pengungkapan Corporate Social Responsibility (CSR) berpengaruh positif terhadap Earning Response Coefficient (ERC), Leverage berpengaruh positif terhadap Earning Response Coefficient (ERC), dan Good Corporate Governance (GCG) diterima untuk ditambahkan dalam model sebagai variabel mediasi atau intervening.